Adding a single pulse into high-frequency pulse stimulations can substantially alter the following episode of neuronal firing in rat hippocampus. (1st February 2023) - Hu, Yifan; Feng, Zhouyan; Zheng, Lvpiao; Xu, Yipeng; Wang, Zhaoxiang
Abstract: Background . High-frequency stimulation (HFS) sequences of electrical pulses are commonly utilized in many types of neuromodulation therapies. The temporal pattern of pulse sequences characterized by varying inter-pulse intervals (IPI) has emerged as an adjustable dimension to generate diverse effects of stimulations to meet the needs for developing the therapies. Objective: To explore the hypothesis that a simple manipulation of IPI by inserting a pulse in HFS with a constant IPI can substantially change the neuronal responses. Approach . Antidromic HFS (A-HFS) and orthodromic HFS (O-HFS) sequences were respectively applied at the alveus (the efferent axons) and the Schaffer collaterals (the afferent axons) of hippocampal CA1 region in anesthetized rats in-vivo . The HFS sequences lasted 120 s with a pulse frequency of 100 Hz and an IPI of 10 ms. In the late steady period (60–120 s) of the HFS, additional pulses were inserted into the original pulse sequences to investigate the alterations of neuronal responses to the changes in IPI. The amplitudes and latencies of antidromic/orthodromic population spikes (APS/OPS) evoked by pulses were measured to evaluate the alterations of the evoked firing of CA1 pyramidal neurons caused by the pulse insertions. Main Results . During the steady period of A-HFS at efferent axons, the evoked APSs were suppressed due to intermittent axonal block. Under this situation, inserting a pulse to shorten an IPI was able to redistribute the following neuronal firing thereby generating an episode of oscillation in the evoked APS sequence including APSs with significantly increased and decreased amplitudes. Also, during the steady period of O-HFS without obvious OPS, a pulse insertion was able to generate a large OPS, indicating a synchronized firing of a large population of post-synaptic neurons induced by a putative redistribution of activations at the afferent axons under O-HFS. Significance . This study firstly showed that under the situation of HFS-induced axonal block, changing an IPI by a single-pulse insertion can substantially redistribute the evoked neuronal responses to increase synchronized firing of neuronal populations during both antidromic and O-HFS with a constant IPI originally. The finding provides a potential way to enhance the HFS action on neuronal networks without losing some other functions of HFS such as generating axonal block.